Fabellae Frammenti di favole latine e bilingui latino-greche di tradizione diretta (III-IV d.C.) - Scappaticcio, Maria Chiara (Untersuchungen zur antiken Literatur und Geschichte, 2018)
Lying between the grammarians` and rhetors` domains, Aesop`s fables were known and employed in the Western and Eastern educational environments mainly for their intrinsically moral essence. Once having explored the literary and grammatical texts concerning the educational role of fables, the book is focussed on the direct witnesses of Latin and bilingual Latin-Greek fables (III-IV AD) coming from the Eastern school environments.